Effect of match-related fatigue on short-passing ability in young soccer players - Rampinini, E.; Impellizzeri, F. M.; Castagna, C.; Azzalin, A.; Bravo, D. F.; Wisloff, U. (Medicine & Science in Sports & Exercise, 2008)
Purpose: To examine whether the fatigue accumulated during match play or determined by short bouts of high-intensity intermittent activities affect short-passing ability in junior soccer players. A further aim was to examine the influence of physical fitness as measured using the Yo-Yo Intermittent Recovery Test (YYIRT) on the changes in short-passing ability after a 5-min simulation of high-intensity activities (HIS).